REPRESENTING THE “HAPPY COPY OF THE EDEN”. RUGENDAS: LANDSCAPE AND NATIONAL IDENTITY IN CHILE, XIX CENTURY. - Cid Rodríguez, Gabriel; Vergara Brunet, Jacinta (Revista de Historia Social y de las Mentalidades, 2012)
The current paper deals with the Chilean national identity building process in the 19th century, through the landscape picture of Johan Moritz Rugendas. Here is analyzed the reformulation of the Chilean territory in national landscape, by means of the work of a traveler artist, and his reception in the society of that time. The representation of landscape in Rugendas connects with a broader national and political project that attempted to make Chile an exception in Latin America, for which the notion of geographic isolation became very important. Likewise, the article develops the connections between Rugendas and thetheoretical propositions of Alexander von Humbolt, a key factor for the understanding of the landscape formulation from the perspective of Romanticism. In this sense, the paper studies the mechanisms of representation of the figure of “the other” that underlies Rugendas’ landscape picture.
Keywords: Rugendas; Nationalism; Identity; Landscape; Territory